Produção de Tithonia diversifolia sob doses de biofertilizante cultivada em sequeiro e irrigado - Matheus Mendes Reis (2016)
Tithonia diversifolia (Hemsl.) A. Gray is a plant originally from Central America and widely distributed in tropical regions. This plant is considered promising food source to ruminants, pigs and poultry, as well as being used as green manure, soil vegetation cover, raw materials for pharmaceutical industry, hedge and windbreak, among others. Despite its potential for multiple use, little is known about the agronomic aspects of Tithonia diversifolia. In this research was evaluated the effects of biofertilizers doses and irrigation on soil chemical properties and onproductivity, growth and leaves chlorophyll and nutrients contents in plants of T. diversifolia. The experimental design was a randomized complete blocks, with three replicates, in a 5 x 2 factorial arrangement, consisting of five biofertilizer doses (0, 20, 40, 60 and 80 m3 ha-1) and two irrigation management (with and without water application via irrigation). When irrigated, plants of T. diversifolia showed higher productivity of dry and green mass, height, leaf area index andleaf K, Zn e B content, however, the irrigation has reduced the content of N, Ca, S, Fe, Mn and chlorophyll in leaves, possibly, because of the presence of bicarbonate in the irrigation water and the dilution effect for greater production of irrigated plants. The increased of dose ofbiofertilizer bovine favored the leaf contents of total, a and b chlorophyll of plants of T. diversifolia irrigated, but did not affect the nutritional aspects, green and dry mass and leaf area for the species. In soil, the biofertilizer doses increase the base saturation and organic matter, P and K contents. Therefore, in regions with low rainfall availability is recommended irrigated cultivation of T. diversifolia, but it is important that new studies clarify the effect of the application of irrigation water with high concentration of bicarbonate in Tithonia diversifolia quality whenused as forage or green manure.